Interpersonal Communication and Sor Theory in “TASTE” Market Snacks in Increasing Customer Loyalty - Kurniawan, Dani; Ifani, Muhammad Zulfi; Nurfaizi, Kevin Rohman (CV. Global Health Science Group, 2023)
Communication is one of the main foundations in running a business. Communication needs to be established to establish relationships between businesses and their customers (Fathurohman & Safitri, 2020). This is intended as a means to find out how to communicate with customers and create product sales targets that suit consumer desires. Based on the existing background, this research aims to analyze interpersonal communication using social theory in the